MBN implementation Barangay Casoroy, San Julian, Eastern Samar - Santiago, Eden V. (Philippine Journal of Public Administration, 1999)
Through the application of the Minimum Basic Needs Approach, Barangay Casoroy, a rural community in the municipality of San Julian, Eastern Samar has palpably improved its condition from a poor barangay with limited access to basic needs and livelihood opportunities to a community characterized by better quality of life among its individual households. Dedicated field workers of various line agencies, the contagious enthusiasm of the municipal technical working group, the competent people's organizations, and supportive barangay leadership succeeded in converging their efforts and steering the community members to act and provide counterpart contribution to local projects addressing the residents' minimum basic needs. The collaborative efforts of the different sectors proved that, indeed, success can be attained even with the barest of resources.